GE_GERICHTE P/9019/2013 vom 11. September 2013 - GE Cour de justice (2013)
VIOLATION DE DOMICILE; PLAN D'AFFECTATION SPÉCIAL; CLÔTURE; AYANT DROIT ; PROCÉDURE ADMINISTRATIVE | CPP.310; CP.186; CP.31; LGZD.3; LAT.14